Monopolistic Competition and Optimum Product Selection - Nocco, Antonella; Ottaviano, Gianmarco I. P.; Salto, Matteo (American Economic Review, 2014)
We provide novel insights on the decentralization of optimal outcomes under monopolistic competition with nonseparable utility, variable demand elasticity, and endogenous firm heterogeneity. Relative to the unconstrained optimum, equilibrium firm selection is too weak, average firm size is too small, low-cost firms are too small, and high-cost firms are too large. The unconstrained optimum can be decentralized through differentiated production subsidies to producers financed through lump-sum taxes on entrants and consumers. When differentiated subsidies and transfers from entrants are not viable, the constrained optimum can be decentralized through a common production subsidy financed by a lump-sum tax on consumers.